Our Classic Stories in Terms of Values Education: The Example of Cevâmi'ü'l-Hikâyât and Levâmi'ü'r-Rivâyât - Selçuk, Bahir; Çelik, Nurten (Abidin Temizer, 2022)
Values are at the forefront of the cultural and social elements that bind the members of nations to each other and hold them together. It is seen that the essence of the basic values has not changed to a large extent in the cultural transfers of the nations from the past to the present. While right, law, justice, tolerance and benevolence prevail in societies where positive values are lived, in societies whose values are turned upside down, chaos and confusion arise in negative behaviors. It is necessary for each individual to take responsibility at the point of teaching and keeping the value judgments alive. Effective and correct transfer of values through education, which is the process of educating people in line with certain goals, will play an extremely important role in establishing social peace and harmony. One of the basic tools that can be used in the transfer of values in the education system is literary texts. Story type texts, especially our classic stories, are among our basic texts that draw attention in terms of values education. Cevâmi'ü'l-hikâyât and Levâmi'ü'r-rivayât, which are one of them and attract attention with their rich content, are among the main works that can be used as a source with the stories written on many subjects such as historical, mythological, moral, and epic. In this study, it is aimed to evaluate the stories in this work, which has been brought to our literature through translation from Persian, in terms of basic values such as justice, friendship, honesty, self-control, patience, respect, love, responsibility, patriotism and benevolence. © 2022, Abidin Temizer. All rights reserved.
DEĞERLER EĞİTİMİ AÇISINDAN KLASİK HİKÂYELERİMİZ: CEVÂMİ’Ü'L-HİKÂYÂT VE LEVÂMİ’Ü'R-RİVÂYÂT ÖRNEĞİ
Keywords: Cevâmi’ü’l-hikâyât and Levâmi’ü’r-rivâyât; classical story; values education